TINJAUAN PELAKSANAAN PERHITUNGAN, PEMOTONGAN, DAN PENYETORAN PPh PASAL 21 PEGAWAI NEGERI SIPIL PADA BADIKLAT PKN BPK RI - Harsanti Riskia Azzahra Surastian (2021)
Taxation is one of the largest sources of revenue in Indonesia. The largest tax in Indonesia comes from the personal income tax of employees and non-employees. One of the taxes levied by the government is income tax article 21 (PPh 21). Article 21 income tax is a tax imposed on income from salaries, wages, honorarium, allowances and other payments earned by domestic individuals. Civil Servants are one of the income recipients who are subject to Article 21 Income Tax deductions. The purpose of this final report is to find out the system for calculating and withholding and depositing Income Tax Article 21 for Civil Servants carried out by Badiklat PKN BPK RI. Based on the writing report, it can be concluded that the application of taxes, especially income taxes on goverment employees, from calculation, withholding, to the payment of tax has been implemented accordance with the Law No. 36 of 2008.